Physiological and transcriptome analyses reveal the photosynthetic response to drought stress in drought-sensitive (Fengjiao) and drought-tolerant (Hanjiao) Zanthoxylum bungeanum cultivars - Hu, Haichao; He, Beibei; Ma, Lei; Chen, Xin; Han, Peilin; Luo, Yingli; Liu, Yonghong; Fei, Xitong; Wei, Anzhi (Frontiers in Plant Science, 2022)
As an important economical plant, Zanthoxylum bungeanum is widely cultivated in arid and semi-arid areas. The studies associated with photosynthesis under drought stress were widely carried out, but not yet in Z. bungeanum. Here, the photosynthesis of two Z. bungeanum cultivars (FJ, Z. bungeanum cv. “Fengjiao”; HJ, Z. bungeanum cv. “Hanjiao”) was analyzed under drought stress using physiological indicators and transcriptome data. Drought decreased stomatal aperture and stomatal conductance (Gsw), reduced transpiration rate (E) and sub-stomatal CO2 concentration (Ci), and lowered chlorophyll and carotenoid content, which reduced the net photosynthetic rate (Pn) of Z. bungeanum. The higher photosynthetic rate in HJ stemmed from its higher chlorophyll content, larger stomatal aperture and Gsw, and higher Ci. Weighted gene co-expression network analysis (WGCNA) identified several ABA signal transduction genes (PYL4, PYL9, and PYR1), LCH-encoding genes (LHCB4.3), and chlorophyll metabolism genes (CRD1, PORA, and CHLH). Additionally, seven transcription factor genes were identified as important factors regulating photosynthesis under drought conditions. In general, a photosynthetic response model under drought stress was built firstly in Z. bungeanum, and the key genes involved in photosynthesis under drought stress were identified. Therefore, the results in our research provide important information for photosynthesis under drought and provided key clues for future molecular breeding in Z. bungeanum.